A Novel Heterozygous Pathogenic Variation in CYCS Gene Cause Autosomal Dominant Non-Syndromic Thrombocytopenia 4 in a Large Chinese Family - Che, Fengyu; Zhao, Jiangang; Zhao, Yujuan; Wang, Zhi; Zhang, Liyu; Yang, Ying (Frontiers in Genetics, 2022)
Aim To determine the etiology of a Chinese family with thrombocytopenia by analyzing the clinical features and genetic variation. Methods Clinical profiles and genomic DNA extracts of the family members were collected for the study. Whole exome sequencing and Sanger sequencing was used to detect the associated genetic variation and verify the family co-segregation respectively. Bioinformatics analysis assessed the pathogenicity of missense mutations. Results The study reported a 3-generation pedigree including 8 family members with thrombocytopenia. The platelet counts of the patients were varied, ranging from 38 to 110×109/L(reference range: 150-450x109/L).The mean volumes and morphology of the sampled platelet were both normal. The bleeding abnormality and mitochondriopathy were not observed in all the patients. Clinical signs of thrombocytopenia were mild. A novel heterozygous missense variant c.79C>T(p.His27Tyr) was identified in CYCS gene associated with autosomal dominant thrombocytopenia. Conclusion We report the first large family with autosomal dominant non-syndromic thrombocytopenia 4 in a Chinese family, a novel heterozygous missense variant 79C>T(p.His27Tyr) was identified. The whole exome sequencing is an efficient tool for screening the variants specifically associated with the disease. The finding enriches the mutation spectrum of CYCS gene and laid a foundation for future studies on the correlation between genotype and phenotype.